Alteration of auditory function in type 2 diabetic and pre-diabetic patients. (3rd June 2018) - Li, Jin; Zhang, Yi; Fu, Xinxing; Bi, Jingtao; Li, Yanhong; Liu, Bo; Zhang, Luo
Abstract: Background: The association between type 2 diabetes mellitus (T2DM) and hearing loss has not been fully investigated and there is little information on the effects of pre-diabetes on alterations in auditory function in Chinese subjects. Methods: The study recruited 51 patients with T2DM, 55 patients with pre-diabetes and 43 control subjects. Auditory function was assessed by pure tone audiometry (PTA) tests and distortion product of otoacoustic emissions (DPOAEs). Tinnitus symptoms were recorded using a medical history questionnaire. Results: A significantly larger number of patients with T2DM (45.1%) were affected by hearing loss, compared to pre-diabetes patients (23.6%; p = .04) and control subjects (25.6%; p = .02), as assessed by PTA. There was no significant difference in PTA between the number of pre-diabetes patients and control subjects. In contrast, mean DPOAEs amplitudes of the pre-diabetes patients were significantly lower than of the control subjects, at all frequencies investigated, except 0.75 kHz. A significantly greater number of pre-diabetes patients reported tinnitus symptoms. Conclusions: Diabetes is associated with bilateral sensorineural hearing loss, especially at high frequencies. While pre-diabetes is not necessarily associated with significant hearing loss, there may be cochlear malfunction, as indicated by DPOAEs. Thus, patients with pre-diabetes who have tinnitus may benefit from DPOAEs and PTA tests.